Knowledge & awareness regarding prevention of cardiovascular disease among medical and nursing students in Universiti Sains Malaysia (USM) - Mishardy, Nur Aisyah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
The Cardiovascular disease (CVD) is one of serious illness that can cause high mortality every year in worldwide (World Health Organization, 2014). Since the urbanization developed years by years, the increment of CVD among young people and its risk factors had become a serious concern in many countries including Malaysia. The aim of this research is to determine the knowledge and awareness on prevention of CVD among medical and nursing students in Universiti Sains Malaysia which the researcher focused between aged 18 to 25 and to identify the association between the level of knowledge and socio-demographic among medical and nursing students in Universiti Sains Malaysia. Cross-sectional designed research was used in this study. A total of 304 students which overall mean was 21.76. Mean age of medical and nursing students that participated in this study was 21.76 years. The majority gender that participated in this study was female with percentage 81.3% (n=247) while percentage for male was 18.8% (n=57). A total of 45.1% medical and nursing students were majority aware that physical activity can reduce the risk of CVD (n=137). There is significant association between level of knowledge of CVD with gender (p=0.014) and source of information (p=0.000). Otherwise, other factors of sociodemographic have no significant association. In conclusion, an effectiveness health education given towards patients will slowly improve their awareness and applied to daily living.